UPAYA MENINGKATKAN KEMAMPUAN MEMBACA NOTASI BALOK MELALUI SISTEM FIXED-DO PADA MATA PELAJARAN ANSAMBEL DI KELAS X-I DI SMA LABSCHOOL KEBAYORAN - Alam, Thirza Maida; Martiati, Lucy; Herdiati, Dian (Program Studi Pendidikan Musik, 2024)
This research aims to improve the ability to read block notation through a fixed-do system. Because in the observation of low block notation reading scores, this is evidenced by the practical assessment and pre-test in Cultural Arts learning. The research method used in this study is a classroom action research method with the Kemmis and Taggart models. Research data was collected through observation, interviews, documentation, and literature studies. Then the data was analyzed using tests and field notes. The research was conducted from February 19 to May 27, 2024 in class X-I at Labschool Kebayoran with a total of 34 students. The number of students who have reached and have not reached the KKM shows an increase in the final score of student evaluation. The results of the study show that the application of the fixed-do system in an effort to improve the ability to read block notation is effective in delivering material about block notation, note value, rest value, and time signature. This method makes it easier for students to memorize the notation layout and understand the material presented because of the fun learning process. This is evident from the increase in the average score of students in each cycle, with an increase of 60.04% from pre-cycle to cycle 1 with an average score of 78.9 students, from these results there are still 11 students who have not reached the KKM. This made the researchers and collaborators decide to proceed to cycle 2. An increase of 17.99% from cycle 1 to cycle 2 with an average score of 93.1 students, from these results there are still 3 students who have not reached the KKM. The benefit of this research is to help read block notation for students.